Иллюзия любви: роман / А. Эшли - Эшли Алисон (Панорама романов о любви, 2010)
Экземпляры: ф-11 (20190902) / Инвентарный номер: 54486 / Цена: 40.00 / Сис.шифр: И (Амер) / Авт.знак: Э 98 / ГРНТИ: 17.82 / ББК: 84(7)